Improved (G′/G)-expansion and extended tanh methods for (2 + 1)-dimensional Calogero–Bogoyavlenskii–Schiff equation - Muhammad Shakeel; Syed Tauseef Mohyud-Din (Alexandria Engineering Journal, 2015)
Traveling wave solutions of nonlinear (2 + 1)-dimensional Calogero–Bogoyavlenskii–Schiff equation are constructed by using improved (G′/G)-expansion and extended tanh-function methods. We demonstrate that some of the obtained exact solutions of these two methods are analogous, but they are not one and the same. The solutions obtained in this article may be imperative and significant for the explanation of some practical physical phenomena. It is observed that improved (G′/G)-expansion method gives a variety of exact solutions. Keywords: Calogero–Bogoyavlenskii–Schiff equation, Extended tanh-function method, Improved (G′/G)-expansion method, Auxiliary equation, Traveling wave solutions